A RETROSPECTIVE IN MOLECULAR AND GENETIC STUDIES OF PRODUCTION-RELATED PATHOLOGY - Анна Геннадьевна Жукова; Лариса Геннадьевна Горохова (Медицина в Кузбассе)
The review summarizes the main research directions at the Molecular-Genetic and Experimental Studies Laboratory. The latest data on the study of the molecular-genetic mechanisms of professionally conditioned pathology development, obtained by the laboratory staff in experimental and clinical studies, are summarized.